2019
DOI: 10.1093/toxsci/kfz056
|View full text |Cite
|
Sign up to set email alerts
|

Sex Modifies Acute Ozone-Mediated Airway Physiologic Responses

Abstract: Sex differences clearly exist in incidence, susceptibility, and severity of airway disease and in pulmonary responses to air pollutants such as ozone (O3). Prior rodent O3 exposure studies demonstrate sex-related differences in the expression of lung inflammatory mediators and signaling. However, whether or not sex modifies O3-induced airway physiologic responses remains less explored. To address this, we exposed 8- to 10-week-old male and female C57BL/6 mice to either 1 or 2 ppm O3 or filtered air (FA) for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 60 publications
4
38
1
Order By: Relevance
“…In allergen sensitized and challenged mice, allergen‐induced AHR and allergen‐induced inflammation are greater in females than in males and castration augments rather than attenuates these effects of allergen (Fuseini et al, ). In contrast, we and others have reported that O 3 ‐induced AHR is greater in male than female mice (Cho et al, ; Birukova et al, ) and we now report that castration attenuates rather than augments responses to O 3 (Fig. ).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In allergen sensitized and challenged mice, allergen‐induced AHR and allergen‐induced inflammation are greater in females than in males and castration augments rather than attenuates these effects of allergen (Fuseini et al, ). In contrast, we and others have reported that O 3 ‐induced AHR is greater in male than female mice (Cho et al, ; Birukova et al, ) and we now report that castration attenuates rather than augments responses to O 3 (Fig. ).…”
Section: Discussioncontrasting
confidence: 55%
“…There is increasing evidence demonstrating the importance of considering sex as a biologic variable. Our data indicate that androgens augment O 3 -induced AHR and likely contribute to the augmented responses to O 3 observed in male versus female mice (Cho et al, 2018a;Birukova et al, 2019). Better understanding of the mechanistic basis for this effect of androgens may ultimately lead to improved treatment of air pollutant exacerbated lung diseases such as asthma.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Exposure to ozone increases BAL concentrations of many cytokines and chemokines that contribute to the neutrophil recruitment and AHR caused by O 3 (Birukova et al, ; Cho, Abu‐Ali, et al, ; Cho et al, ; Kasahara et al, ; Mathews et al, , ; Tashiro et al, ). To determine whether there were vendor‐ and/or housing‐related differences in the production of these inflammatory moieties following O 3 exposure, we performed a multiplex assay (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In male mice, the magnitude of AHR induced by ozone exposure is decreased by both antibiotic treatment and GF conditions (Cho et al, ). The magnitude of ozone‐induced AHR is greater in male than in female mice (Birukova et al, ; Cho, Abu‐Ali, et al, ; Kasahara et al, ), and this sex difference is abolished when mice are treated with antibiotics (Cho, Abu‐Ali, et al, ). Furthermore, when weanling female pups are housed in cages conditioned by adult male mice, they develop greater ozone‐induced AHR than weanling female pups raised in cages conditioned by adult females (Cho, Abu‐Ali, et al, ).…”
Section: Introductionmentioning
confidence: 99%